Post a New Question

trig

posted by .

Please help me how to do this:
1) 1 + sina*cosa / (cosa + sina)^2 =
2) sina + cosa / 1- 2sin^2a =

  • trig -

    Are you sure the first one isn't
    ( 1 + 2sina cosa)/(cosa + sina)^2 ?
    because then it would be
    = (sin^2a + cos^2a + 2sina cosa)/(cosa + sina)^2
    = (sina + cosa)^2/(cosa + sina)^2
    = 1

    2nd:
    (sina + cosa)/(1 - 2sin^2a)= (sina + cosa)/(sin^2a + cos^2a - 2sin^2a)
    = sina+cosa)/( cos^2a - sin^2a)
    = (sina + cosa)/( cosa - sina)(cosa+sina) )
    = 1/(cosa - sina)

  • trig -

    oh yes, I wrote the first one wrong.
    THANK YOU

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question